Секреторная функция скелетных мышц: механизмы продукции и физиологические эффекты миокинов - Капилевич Л. В. Леонид Владимирович; Кабачкова А. В. Анастасия Владимировна; Дьякова Е. Ю. Елена Юрьевна; Захарова А. Н. Анастасия Николаевна; Лалаева Г. С.; Кироненко Т. А. Татьяна Александровна; Орлов С. Н. Сергей Николаевич (2016, 2016)
Заглавие с экрана